Reactivity of U-E-U (E = S, Se) toward CO2, CS2, and COS: New mixed-carbonate complexes of the types U-CO2E-U (E = S, Se), U-CS2E-U (E = O, Se), and U-COSSe-U - Lam, Oanh P.; Franke, Sebastian; Heinemann, Frank Wilhelm; Meyer, Karsten (Journal of the American Chemical Society, 2012)
We recently reported the formation of a bridging carbonate complex [((ArO)N)U(μ-η: κ-CO)] via reductive cleavage of CO, yielding a μ-oxo bridged complex, followed by the insertion of another molecule of CO. In a similar strategy, we were able to isolate and characterize a series of mixed carbonate complexes U-COE-U, U-CSE-U, and even U-OC(S)Se-U, by reacting bridged chalcogenide complexes [((ArO)N)U(μ-E)] (E = S, Se) with CO, CS, and COS. These chalcogenido mixed-carbonate complexes represent the first of their kind. © 2012 American Chemical Society.